Science, development, and violence : the revolt against modernity - Alvares, Claude Alphonso (Delhi ; New York : Oxford University Press, 1992)
Study in the Indian context.
Spine title: Science, development & violence.
Includes bibliographical references (p. 64-74) and index.
Keywords: Economic development; Science; Ecology; Progress